Sustainability assessment of Vietnam's electricity planning: Using section 1 of the 2009 hydropower sustainability assessment protocol - Dao Trong Tu; Le Thi Thuy Quynh; Pham Quang Tu; Bach Tan Sinh (Australian Government Aid Program, M-POWER and CGIAR Challenge Program on Water and Food, 2011)
The Draft Hydropower Sustainability Assessment Protocol (HSAP) was first introduced in Vietnam at the National Consultant Workshop organized by Vietnam Water Partnership (VNWP) in November 2009. Although the structure of HSAP is relatively complex and new to Vietnam, the participants (from Government agencies, experts, investors, and Vietnamese and international civil society organizations) had the impression that the HSAP has the potential to be a useful tool for participatory assessment of the sustainability of a hydropower project and broader planning. With the assistance of the M-POWER (Mekong Program on Water, Environment and Resilience), a national group of experts in multiple disciplines from government agencies, national organisations and NGOs was mobilized to conduct a rapid sustainability assessment of the energy and hydropower development policy and plan in Vietnam. Section I of the draft HSAP 2009 was used as an assessment tool. The assessment focused on the quality of the process of developing and implementing the strategic development of the electricity sector in general and hydropower development of Vietnam in particular. Even though the rapid assessment framework of HSAP was quite new to the Assessment Team and the assessment subjects are broad, the Team and participants in this trial learned positive and negative lessons that can serve as a basis for future assessment exercises to enable deeper and more comprehensive assessment. The assessment report includes four major parts: 1) Introduction and background, 2) Water and hydropower development in Vietnam; 3) Rapid assessment - process and discussion of results; and 4) Lessons learned from the assessment and recommendations for draft HSAP 2009.